Hypoventilation training at supramaximal intensity improves swimming performance - Woorons, X.; Mucci, P.; Richalet, J. P.; Pichon, A. (Medicine & Science in Sports & Exercise, 2016)
Purpose: This study aimed to determine whether hypoventilation training at supramaximal intensity could improve swimming performance more than the same training conducted under normal breathing conditions.